Genome reconstruction reveals distinct assemblages of Gallionellaceae in surface and subsurface redox transition zones. Issue 5 (9th March 2020) - Bethencourt, Lorine; Bochet, Olivier; Farasin, Julien; Aquilina, Luc; Borgne, Tanguy Le; Quaiser, Achim; Biget, Marine; Michon-Coudouel, Sophie; Labasque, Thierry; Dufresne, Alexis
ABSTRACT: Fe-oxidizing bacteria of the family Gallionellaceae are major players in the Fe biogeochemical cycle in freshwater. These bacteria thrive in redox transition zones where they benefit from both high Fe concentrations and microaerobic conditions. We analysed the Gallionellaceae genomic diversity in an artesian hard-rock aquifer where redox transition zones develop (i) in the subsurface, where ancient, reduced groundwater mixes with recent oxygenated groundwater, and (ii) at the surface, where groundwater reaches the open air. A total of 15 new draft genomes of Gallionellaceae representing to 11 candidate genera were recovered from the two redox transition zones. Sulfur oxidation genes were encoded in most genomes while denitrification genes were much less represented. One genus dominated microbial communities belowground and we propose to name it ' Candidatus Houarnoksidobacter'. The two transition zones were populated by completely different assemblages of Gallionellaceae despite the almost constant upward circulation of groundwater between the two zones. The processes leading to redox transition zones, oxygen diffusion at the surface or groundwater mixing in subsurface, appear to be a major driver of the Gallionellaceae diversity. Abstract : Genome reconstruction of Gallionellaceae dwelling in groundwater of a fractured aquifer suggests niche partitioning linked to the physical nature of the oxic-anoxic interface developing belowground and at the surface.